THE INVOLVEMENT OF FATHER IN ORDER TO GIVE NUTRITIOUS FOOD FOR CHILDREN - Tri Ratna Ningsih; Ariu Dewi Yanti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
The under five children age is a nutritionally vulnerable group,therefore they require treatment including physical care with the provision of nutritious food especially from the father and mother. The purpose of this research is to know the involvement of father in giving nutritious food to under five children Mojokerto District. The research design is descriptive. The population is all fathers who have under five children as many as 38 people, taken entirely as a sample by using total sampling. The research variable is father's involvement in giving nutritious food to children. Data analysis using percentage.The results showed that most of father's involvement in nutritious food feeding on under-five children is not good as much as 23 people (60,5%). This is motivated by the status of the father who worked as an entrepreneur or not working, elementary education, 36-60 month old childrren and male sex, and working mothers.Time-consuming job as an entrepreneur plus a basic education leads children to may be financially fulfilled but less good in emotional and behaviour involvement. Moreover, the status of unemployment and basic education leads to poor financial and emotional support and behavior. 36-60 months of age and male sex is an active children and tend to be closer to the mother so the father is less involved. Similarly, the status of working mothers does not make the father more involved, because the father tends to require him to work that sacrifice togetherness with children.